Angiosarcoma Mimicking Rhinophyma. (17th May 2010) - Lo Presti, Maurizio; Mazzella, Caterina; Monfrecola, Ambra; Falleti, Jessica
Abstract : We report the case of a 61-year-old man showing persistent erythematous macules, plaques, and partially confluent nodules with irregular borders, developed on his nose for one year. During that time the patient underwent several dermatological consultations, and all produced the same diagnosis: rhinophyma. So antibiotic and steroid treatment was carried out without any improvement while the lesions kept growing. When the patient came to our observation, physical examination revealed large, infiltrative, oedematous, erythematous plaques and rare nodules, with superficial telangiectatic vessels. Cervical lymphadenopathy was not detectable. Routine laboratory analysis was normal. Punch biopsy was performed, and histopathology and immunohistochemical studies were consistent with cutaneous angiosarcoma. This is the report of a face angiosarcoma with an unusual and very deceptive clinical presentation.